RANKING THE SPECTATORS' DIFFICULTIES IN PURCHASING ELECTRONIC TICKETS OF FOOTBALL PREMIER LEAGUE - Ahmad Narimani; Tahare Moosavi Rad; Loghman Keshavarz (ümit doğan üstün, 2017)
This study aimed to rank the spectators' difficulties in buying electronic tickets of football premier league matches at Azadi stadium. The population consisted of all spectators of Esteghlal-Persepolis match in the fifteenth league at Azadi stadium (N= 100000). According to Morgan table and using simple random sampling method, 500 participants were selected as sample. A researcher-made questionnaire was used for collecting the data; its face validity was confirmed by 15 experts and performing a pilot study on 30 subjects, its Cronbach's alpha was calculated to be 0.86. Using SPSS 22, the descriptive and inferential (including Friedman test) statistics was applied for analyzing the data. The findings showed that there was a significant difference between rankings of difficulties in buying electronic tickets of Football premier league matches at Azadi Stadium. The difficulties were ranked as: problem in ticket systems, early selling out of electronic tickets, lack of confidence to electronic ticket sale, lack of skill to work with the internet, low speed of internet, and lack of access to the internet